The effect of career development, work-life balance, and remuneration on employee job satisfaction: Evidence from the Badan Pendapatan Daerah (BAPENDA) of Tangerang Regency - Meilyasih Rohana Lumban Toruan; Narti Eka Putri; Ferdian Agustiana (Priviet Social Sciences Journal, 2026)
This study aims to examine the influence of career development, work-life balance, and remuneration on employee job satisfaction at the BAPENDA of Tangerang Regency. Employee job satisfaction serves as a crucial indicator of human resource management effectiveness, particularly in the public sector where optimal service delivery and professional conduct are essential. This study adopted a quantitative approach that utilized a causal-comparative design. Data were gathered using questionnaires distributed to 115 employees selected through proportional cluster random sampling. Analysis was performed using multiple linear regression in SPSS, including validity tests, reliability assessments, classical assumption tests, and partial t-tests. The results indicate that career development and remuneration exert positive and significant influences on employees job satisfaction, whereas work-life balance exhibits a significant negative effect. These results highlight the distinct contributions of each variable in shaping job satisfaction. Notably, the negative effect of work-life balance suggests that, within high-pressure public sector environments, work-life balance may reflect underlying role conflict rather than actual equilibrium. Therefore, strategic human resource management initiatives should not only optimize career development systems and remuneration schemes, but also address structural workload issues to effectively enhance employee job satisfaction.